POLA PEMBELAJARAN KOOPERATIF MODEL JIGSAW BAGI SISWA SEKOLAH - Sumekto, Didik Rinan (MAGISTRA, 2011)
Cooperative learning covers either academic assignments or social goals. The important aspects ofcooperative learning herewith are to assist students in developing the cooperative behaviors by implementinga good relationship among them mutually to any subject matters mastery they are learning for. The complexlearning assignments, such as solving the problems, adopting critical thinking, analyzing the matters, andlearning the concepts are applicably needed to the cooperative learning concept. Cooperative learning reflectsviews in which students may learn it from their own active participation and empirical experience through thesmall groups. These activities will help students to learn the social skills accordingly, besides they may mutuallydevelop democratic behaviors, logical thinking skills, and creative quality improvements as well.The jigsaw model cooperative learning adopts some students potencies to interact with each other. Thislearning model is intended to stimulate the cooperative capability in critical and analytical thinking and toassist students who have insufficient understanding to any subject matters. The heterogenic participants (race,religion, social and economic strata, learners capability, etc.) of the jigsaw learning model are chosen randomly.The randomly group members determination will benefit to students, because they are able to fit their self-adaptability as well as this condition is fair-regarded. The teachers role in the jigsaw model is as a facilitator,skills trainer, controller to the learning process, motivator to students mutual responsibility and evaluator tothe multiple perspectives on the subject matters given.Key words: Active learning, higher-order thinking skills, teacherstudent and student student interaction